1978
DOI: 10.1172/jci108946
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Attachment of Neutrophils to Candida albicans Pseudohyphae in the Absence of Serum, and of Subsequent Damage to Pseudohyphae by Microbicidal Processes of Neutrophils In Vitro

Abstract: A B S T R A C T Mechanisms were studied that might explain the attachment and damage to Candida albicans pseudohyphae by neutrophils in the absence of serum. Attachment of neutrophils to pseudo hyphae was inhibited by Candida mannans (1-10 mg/ml), but not by mannose, dextran, chitin, conconavalin A, or highly charged polyamino acids. Contact was also inhibited by pretreatment of Candida before incubation with neutrophils with chymotrypsin, but not trypsin or several inhibitors of proteases. Similar results wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
55
0
1

Year Published

1980
1980
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(64 citation statements)
references
References 49 publications
(56 reference statements)
8
55
0
1
Order By: Relevance
“…In the presence ofmyeloperoxi- INTRODUCTION In previous studies in our laboratory, it was established that pseudohyphal and hyphal forms of Candida albicans could be damaged and probably killed by nonphagocytic mechanisms of human neutrophils in vitro (1). Experimental data indicated that Candida hyphae, though too large to be ingested, activated microbicidal mechanisms of neutrophils and caused specific release of neutrophil lysosomal enzymes (2). Indirect evidence supported the impression that oxidative mechanisms ofneutrophils were more important hian nonoxidative mechanisms in damaging hyphae.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…In the presence ofmyeloperoxi- INTRODUCTION In previous studies in our laboratory, it was established that pseudohyphal and hyphal forms of Candida albicans could be damaged and probably killed by nonphagocytic mechanisms of human neutrophils in vitro (1). Experimental data indicated that Candida hyphae, though too large to be ingested, activated microbicidal mechanisms of neutrophils and caused specific release of neutrophil lysosomal enzymes (2). Indirect evidence supported the impression that oxidative mechanisms ofneutrophils were more important hian nonoxidative mechanisms in damaging hyphae.…”
mentioning
confidence: 93%
“…In preliminary experiments, neutrophils from a single patient with chronic granulomatous disease failed to damage Candida hyphae (2). Moreover, inhibitors of potential nonoxidative microbicidal mechanisms, such as cationic proteins and lactoferrin, failed to alter damage to hyphae by normal neutrophils (2).…”
mentioning
confidence: 99%
See 3 more Smart Citations